Core close-up images of IODP Hole 389-M0099C - Webster, Jody M; Ravelo, Ana Christina; Grant, Hannah; Stewart, Margaret S; Rydzy, Marisa; Le Ber, Erwan; Allison, Nicola; Asami, Ryuji; Boston, Brian; Braga, Juan-Carlos; Brenner, Logan; Chen, Xuefei; et al. (PANGAEA, 2025)
Collection of split cores' close-up images from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai'i, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. Close-up photos were taken utilizing a standard photo camera by sedimentologists during visual core description of the archive half. Decision on imaged intervals was subject to the core describers in charge. The standard IODP convention for labelling follows the syntax Exp-SiteHole-CoreCoretype-Section_ImageName_IntervalTop [in cm in section]-IntervalBottom [in cm in section]. For example, a file 389-M0096A-02R-2_Picritic-Basalt_1-18.jpg identifies a close-up image of picritic Basalt from section 2 interval 1 – 18 cm of core 2R (R indicating rotary coring method), from Hole M0096A from Expedition 389. For further methodological information see methods chapter in Webster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025
Keywords: central Pacific; Coral Reef; Earth climate feedbacks; Earth history tipping points; Expedition 389; Hawaiian Drowned Reefs; Hawaiian geology; International Ocean Discovery Program (IODP); MMA Valour; Paleoclimate; sea level; volcanic